Complex Treatment of Chronic Adenoiditis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In the period from 2021 to 2022, we examined 70 children who applied to the Bukhara Regional Children's Multidisciplinary Medical Center ENT department. The age distribution was as follows: children of the first year (7 months to 11 months) – 2 (3%), early age (from 1 to 2 years) – 16 (22.8%), preschool (3 l – 6 years) - 33 (47.2%) and school age (7 l – 11 years old) – 19 (27.3%) children. Patients of preschool age (from 3 to 6 years, 47.2%) prevailed among the patients.The use of photodynamic therapy in the complex therapy of chronic adenoiditis eliminates tubar dysfunction and snoring 5 times faster and normalizes nasal breathing 3 times faster than with traditional treatment, improving the indicators of anterior active rhinomanometry in total volume flow 4 times, and in total resistance 20 times, which indicates adequate inclusion of hypertrophied pharyngeal tonsil to the zone of therapeutic effect of the new method.